Probiotic Formulations Containing Fixed and Essential Oils Ameliorates SIBO-Induced Gut Dysbiosis in Rats - Ismail Aslan; Leyla Tarhan Celebi; Hulya Kayhan; Emine Kizilay; Mustafa Yavuz Gulbahar; Halil Kurt; Bekir Cakici (MDPI AG, 2023)
Dysbiosis of the gut microbiota is associated with the pathogenesis of intestinal diseases such as inflammatory bowel disease, irritable bowel syndrome (IBS), small intestinal bacterial overgrowth (SIBO), and metabolic disease states such as allergies, cardiovascular diseases, obesity, and diabetes. SIBO is a condition characterized by an increased number (>1 × 103 CFU) of abnormal bacterial species in the small intestine. Interest in SIBO has gained importance due to increased awareness of the human microbiome and its potential relationships with human health and disease, which has encouraged new work in this area. In recent years, standard antibiotic regimens (rifaximin and metronidazole) have been used to treat SIBO, but solo antibiotics or their derivatives are insufficient. In this study, the therapeutic effects of the probiotic form, which contains coconut oil and traces of peppermint-lemon-patchouli essential oil, were evaluated on the Dysbiosis-Based Rat SIBO Model. There are significant differences between sick and healthy rats (p = 0.014), between sick rats and rats treated with the oil mix plus probiotic mix protocol (p = 0.026), and between rats treated with only the probiotic and only oil protocols (p = 0.030) in the evaluation of TNF-α levels. Histologically, villi distortion and loss of crypts, epithelial shedding and necrotic changes in the apical regions of the villi, and inflammatory cell infiltrations extending to the lamina propria and submucosa were observed in sick rats. Mitotic figures in villus epithelium and crypts were observed in rats treated with 9.2 × 109 CFU/1000 mg/coconut oil + trace amounts of peppermint-lemon-patchouli essential oil and a probiotic mixture (oil + probiotic mix protocol). A regression of inflammatory reactions and an increase in goblet cells were observed. A decrease was observed in inflammation markers in sick rats. On the other hand, the oil plus probiotic mix protocol recovered digestive system defects in the animals caused by dysbiosis. In the future, these treatment approaches can be effective in the treatment of SIBO.